Life-and-Death Decision-Making by p53 and Implications in Cancer Immunotherapy - Liu, Yong (Trends Cancer, 2020)
The tumor suppressor p53 is mutated in approximately half of all cancers, whereas the p53 signaling network is perturbed in almost all cancers. In response to different stress stimuli, p53 selectively activates genes to elicit a cell survival or cell death response. How p53 makes the decision between life and death remains a fascinating question and an exciting field of research. Understanding how this decision is made has major implications in improving cancer treatments, particularly in recently evolved immune checkpoint inhibition therapy. Here, we highlight progress and challenges in understanding the mechanisms governing p53’s life-and-death decision-making process, and discuss how this decision is relevant to immune system regulation. Finally, we discuss how knowledge of the p53 pro-survival and pro-death decision node can be applied to optimize immune checkpoint inhibitor therapy for cancer treatment.